Latent Dimensions of the Counselor Rating Form and the Counseling Evaluation Inventory - Bachelor, Alexandra; Salamé, Ramzi (Canadian Journal of Counselling and Psychotherapy, 2007)
Although thev are extensively used to assess counsellor performance, the construct validity of rating scales such as the Counselor Rating Form (CRF) and the Counseling Evaluation Inventory (CEI) has been challenged because of the observed statistical overlap both within and across these theoretically different measures. In contrast to previous studies based on raw scores, we examined the extent to which dimensions of the CRF and CEI represent similar constructs when controlling for intra-measure overlap through the use of factor scores. Factor scores derived from separate factor analyses of CRF and CEI ratings, obtained from 230 undergraduates viewing videotaped excerpts of therapy sessions, were submitted to a second-order factor analysis. Three higher-order factors were identified, accounting for 66% of the total variance, each of which contained a dimension from each measure. The use of factor scores thus resulted in a clearer separation of individual scales, supporting the purported multidimensionality of each measure, yet similarities between the two measures were also observed.